Physiological and root morphological responses in different combinations of rootstock-scion of cacao to water deficit - Jaimez, Ramón; Vásconez, Gregorio; Sotomayor, Ignacio; Quijano, Grisnel; Morante, Jaime; Arteaga, Francisco; Cedeño-Garcia, George (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Grafting is a common practice in cacao cultivation, but it has not been reported whether rootstock-scion combinations respond differently in terms of water transport, growth, or nutrient uptake under varying soil water availability conditions. The effects of water deficits on water potential (Ψf), basal diameter (db), root growth, chlorophyll and leaf concentrations of nitrogen (N) were evaluated in 16 rootstock-scion combinations that resulted from four rootstocks and four scion clones. Grafted seedlings were subjected to two water regimes: 21 days without irrigation (WD) and continuous irrigation (I). Under WD conditions, Ψf tended to be lower when using the EETP800 clone with the four rootstocks, indicating that this clone may have a higher rate of transpiration. The greater Ψf (p <0.05) obtained with the EET400 and EET399 rootstocks-scion combinations indicate higher water uptake capacity by the root systems of these rootstocks, which permits the maintenance of adequate transpiration rates and higher Ψf. The higher db, chlorophyll content and leaf N content obtained in the combinations of scions with the EET400 rootstock under WD impart on this rootstock a more favorable degree of adaptability for tolerating water deficits. However, this tolerance is not associated with increased root growth, which indicates that higher efficiency of water uptake is related to metabolic and physiological processes rather than a larger root surface.